Temperature-dependent modeling and enhanced measurement of ultrasonic velocity in LAS glass–ceramics - Wenqing Wei; Xue Qi; Zisheng Tang; Hu Deng; Hong Liu (Scientific Reports)
Abstract Li2O–Al2O3–SiO2 (LAS) glass–ceramics are widely used in many fields owing to their ultra-low coefficient of thermal expansion (CTE). The ultrasonic velocity method shows potential as an effective method for the nondestructive measurement of the CTE and CTE homogeneity of large LAS glass–ceramics. To further improve the precision of ultrasonic velocity (c L) measurements of LAS glass–ceramics and reveal the effect of the temperature (T) on c L, an improved correlation method to rapidly determine the time of flight (TOF) in LAS glass–ceramics is proposed. The proposed method significantly reduces the calculation time by a factor of 100 for LAS glass–ceramics with a thickness of 50 mm. Furthermore, the TOF results obtained by this method were compared with those obtained by the commonly used peak and zero-crossing methods. The proposed correlation method showed better TOF repeatability precision (0.69 ns). Considering the effect of T on the precision of the c L measurement, a c L–T exponential model was developed based on the theoretical c L–T analytical model. The accuracy of the c L–T exponential model was experimentally verified. The root-mean-square error was within 0.30 m/s, which shows that the developed exponential model can reliably predict the c L values of LAS glass–ceramics at different temperatures. The two meaningful findings mentioned above provide methodological and modeling support for high-precision nondestructive CTE testing of large LAS glass–ceramics at specific temperatures.